A later bronze age shield from South Cadbury, Somerset, England - Coles, J. M.
A shield of beaten bronze from South Cadbury, Somerset, England is the first shield to be discovered by excavation on an archaeological site. The shield lay in a silt-filled Bronze Age ditch on a spur of land below Cadbury Castle. A stake was thrust through the shield. The paper considers the recovery and conservation of the shield, the technology of metal shields and the evidence for the ritual deposition of shields in the Later Bronze Age of western Europe.